A comparison of UP‐PCR and RAPD markers to study genetic diversity of Fusicladium effusum (G. Winter), cause of pecan scab. Issue 4 (26th February 2014) - Bock, C. H.; Endalew, T. T.; Biswas, B. K.; Yadav, A. K.; Sitther, V.; Hotchkiss, M. W.; Stevenson, K. L.; Wood, B. W.; Klopfenstein, N.
Summary Fusicladium effusum infects pecan causing yield loss, but no information is available on the genetic diversity of F. effusum. Randomly amplified polymorphic DNAs (RAPDs) and universally primed polymerase chain reaction (UP‐PCR) were compared to detect polymorphisms on a group of 20 isolates of F. effusum from 11 geographical locations in the southeastern USA. Two tests (run 1 and 2) of both the RAPD and UP‐PCRs were conducted to assess the repeatability of the methods, and the markers scored on agarose gels. In addition, the UP‐PCR markers from run 1 were scored using an automated capillary system. Both RAPDs and UP‐PCR markers detected a high level of polymorphism among the scored markers (92 and 91% of RAPD markers, and 86 and 87% of manually scored UP‐PCR markers in run 1 and 2 were polymorphic, respectively; 93% of UP‐PCR markers were polymorphic when scored using the automated system). Unweighted paired group method of arithmetic averages (UPGMA) analysis showed both RAPDs and UP‐PCR markers individually identified each isolate, producing three groupings, but only the groupings based on run 1 and 2 of the UP‐PCR contained the same isolates. Bootstrap analysis based on the Dice coefficient produced phenograms from the UP‐PCR data with weak to moderate node support (≥54) for the primary branch, but no support for the RAPDs data (≤34). A Mantel test of runs 1 and 2 using RAPDs or UP‐PCR showed good agreement (r = 0.8761 and 0.8289, p < 0.0001), but poor agreement between RAPDs and UP‐PCR. UP‐PCR results based on the interisolate Dice coefficients showed a weak to strong association with distance. Based on these results, both RAPDs and UP‐PCR markers were capable of demonstrating polymorphisms and identifying relationships among isolates of F. effusum; however, UP‐PCR markers appear to be more reliable.